Mental health law in the community: thinking about Africa - Bartlett, Peter; Jenkins, Rachel; Kiima, David (BioMed Central, 2011)
The new United Nations Convention on the Rights of Persons with Disabilities creates a new paradigm for mental health law, moving from a focus on institutional care to a focus on community-based services and treatment. This article considers implementation of this approach in Africa.